ASXAQ IS A PHYSIOLOGICALLY ACTIVE MEDICATION USED TO TREAT AND PREVENT PERSISTENT CONSTIPATION IN PEOPLE - Ibragim R. Askarov; Khabibullo N. Kodirov (Western European Studies, 2025)
The article discusses the distribution areas of ASXAQ . the nature of enhancing intestinal function, the vitamin-rich properties that the gut requires, and the use of the physiologically active drug ASXAQ in patients with persistent constipation. Chronic constipation has been shown to be the most successful treatment and preventative measure for clinical signs., as well as data on the mechanism of action on the colon wall and their discussion.
Keywords: Constipation; ASXAQ; qulaty of life